The chronic disease concept of addiction: Helpful or harmful?. (August 2015) - Wiens, Thomas K.; Walker, Lawrence J.
Abstract In contemporary culture, socially deviant behaviour is increasingly being conceptualised as the result of a disease; most salient perhaps, in regards to addiction. This chronic disease model of alcoholism has its roots in early assumptions that have recently been discredited or at least challenged. This study employs an experimental method to examine whether telling individuals with a mild to moderate alcohol addiction that they have a chronic brain disease influences their perceptions of addiction-related agency as well as their feelings of shame and stigma. Participants, recruited online, were randomly assigned to internalise statements promoting (a) a disease model of addiction, (b) a psychosocial model or (c) a neutral control condition; they then completed several indices of agency in relation to drinking, as well as measures of stigma and shame. Participants who internalised the disease model of addiction tended to have weaker perceptions of drinking self-efficacy, whereas internalising psychosocial model beliefs tended to induce a stronger internal locus of control and weaker entitisation of addiction. Both the disease and the psychosocial conditions increased, in comparable amounts, feelings of stigma and shame relative to the control condition. This study provides empirical support to the notion that framing addiction within a biological conceptualisation, as opposed to a psychological and social framework, weakens perceptions of agency in relation to drinking. Likewise, no evidence was found to support the common assertion that the disease model reduces feelings of stigma and shame.